RELATIONS OF WORKERS AND COUNTRIES IN THE MINIMUM CENTER OF MINIMUM CITY OF PEKANBARU IN 2017 - Arman, Rival Dalasia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The problem lately is after 15 years of reformation, the labor movement seems to be seen only as a collection of pragmatic masses who only struggle to demand a wage increase rather than a movement that has root ideology and political platform. This assumption will be tried to be proved by this essay by starting from the basic question, is the labor movement now pragmatic about the issue orientation of its movement, that is merely fighting for the issue of wage increase or does the union now develop the orientation of the movement issue that is not merely the struggle of the issue of wage increase? It is, therefore, interesting to trace the various issues that the post-reform labor movement really struggles with.This paper will address the issue of what the union struggle for in the realm of regional autonomy and the struggle of urban workers. This study rests on the basis of the theory of industrial relations between labor and state in the determination of wages. Labor conditions in urban and non urban areas are different since the number of decent living needs in the two conditions is also different. The interaction between labor, trade union, state and employers became the focus of attention in this study. Moving from that condition, this study was conducted with qualitative approach with descriptive research type. The data collected are grouped into primary and secondary data types for further processing with technical qualitative data analysis triangulation.This study found that the process of determining the district minimum wage in Pekanbaru City is in accordance with legislation with respect to minimum wage. The regulation concerning minimum wage setting mechanism is regulated in Law Number 13 Year 2003 and Decree of Minister of Manpower and Transmigration Number 226 Year 2000 About Amendment Article 1, Article 3, Article 4, Article 8, Article 11, Article 20 and Article 21 Permenakertrans Number Per- 01 / MEN / 1999 on Minimum Wage. The wage stage is done by the wage council which is established by Presidential Decree Number 107 Year 2004 About Wage Council. This determination process begins with the preparation of a survey by the Wage Council to review directly to the market with regard to the price of the needs consumed by the community with the size of single men / women according to Permenakertrans No. PER./17/MEN/VII/2005 on Components and the Implementation of the Stages of Achieving the Decent Living Needs. The relationships established between workers and the government are only manifested in the discussion room of the Wage Council with an unrepresentative portion of the labor vote. The issue of the deployment of workers' representatives also causes the labor vote to be limited. In addition, the wage council is also widely filled by people near the Mayor.Keywords: Wages, Policy, Industrial Relations